An Appendix Origin Burkitt’s Lymphoma Spreading into Genital Tract - Mustafa Ulubay; Fahri Burçin Fıratlıgil; Uğur Keskin; Ulaş Fidan; Mehmet Gamsızkan; Müfit Cemal Yenen; Ali Ergün (Gynecology Obstetrics & Reproductive Medicine)
Burkitt’s lymphoma (BL) occurs commonly in children and young adults, whereas bilateral ovarian involvement is extremely rare. We report a patient with unusual symptoms for BL, mimicking an ovarian neoplasm. Here, our aim was also to point out that BL can spread into the genital tract.